1993
DOI: 10.1007/bf01371378
|View full text |Cite
|
Sign up to set email alerts
|

No attentional bias for pictoral stimuli in spider-fearful subjects

Abstract: A number of experiments have shown that (spider) fearful subjects direct their attention to fear-relevant words, even when these words are irrelevant to the completion of a target task (e.g., color naming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…Sexual stimuli produced a strong effect that matches the effect of strong unpleasant pictures (Buodo et al, 2002). In contrast, evolutionary threat pictures had a much weaker effect that failed to reach significance in the present studies (Merckelbach et al, 1993). Subsequently, I discuss the implications of the results for the three major theories of emotional influences on attention and for process models of emotions.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Sexual stimuli produced a strong effect that matches the effect of strong unpleasant pictures (Buodo et al, 2002). In contrast, evolutionary threat pictures had a much weaker effect that failed to reach significance in the present studies (Merckelbach et al, 1993). Subsequently, I discuss the implications of the results for the three major theories of emotional influences on attention and for process models of emotions.…”
Section: Discussioncontrasting
confidence: 93%
“…First, evolutionary threat pictures failed to be significantly different from neutral pictures. It is important to note that several other studies with similar stimuli (snakes or spiders) have failed to find significant differences between neutral and evolutionary threat stimuli (Kindt & Brosschot, 1999;Merckelbach et al, 1993). Other studies have found differences between neutral and evolutionary threat stimuli of the same magnitude (ϳ20 ms), and the difference was significant because of larger power (e.g., Thorpe & Salkovskis, 1998).…”
Section: The Evolutionary Threat Hypothesismentioning
confidence: 94%
See 1 more Smart Citation
“…This work is broadly consistent with results from spider phobia studies using the modi®ed Stroop task with pictorial stimuli, which have provided evidence of an attentional bias for fear-related stimuli in phobic individuals (e.g. Kindt & Brosschot, 1997 ;Lavy & van den Hout, 1993 ; but see Merckelbach, Kenemans, Dijkstra & Schouten, 1993, for a null result with another interferencebased task).…”
supporting
confidence: 87%
“…However, no threat specific interference in phobic participants was found after adjusting for individual differences in overall color-naming speed. The failure to find threat specific attentional biases in spider phobic participants is consistent with prior studies (e.g., Merckelbach, Kenemans, Dijkstra, & Schouten, 1993;Wenzel & Holt, 1999). However, inspection of the means and SDs in Table 2 indicates that the spider-neutral interference in the spider phobic group in the exposure condition is the highest of the interference scores.…”
Section: Discussionsupporting
confidence: 83%